Implikasi Dasar dan Landasan Pendidikan Islam terhadap Pengembangan Kurikulum dan Pembelajaran - Ovi Mardatillah; Qonita Wardah; Gusmaneli (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Islamic education is a comprehensive development process that integrates spiritual and intellectual aspects based on the teachings of the Qur'an and Sunnah. The curriculum is designed as an effort to form individuals who are faithful, have noble morals, and are able to face the development of the times wisely. The role of teachers is not only limited to conveying knowledge, but also being role models in instilling Islamic values. The learning approach is designed comprehensively and contextually to support the development of student character. The integration between the curriculum, learning strategies, and the role of educators is the key to producing a generation of Muslims who excel in morals and knowledge.